The Impact of Board Members Accounting Expertise on Dividends Policy: The Moderator Role of Gender Diversity-Evidence from Jordan - Zalloum, Nidal Omar; Al-Qteishat, Hussam Saher (Jordan Journal of Business Administration, 2025)
This study aimed to determine the impact of the accounting expertise of board members on dividends policy in industrial companies listed in the Amman Stock Exchange. It also examined the moderation of gender-diversity adjustment of the board members in the relationship between accounting expertise and dividends policy. The study sample consisted of (29) companies that met the study criteria, representing (70.7%) of the study population of (41) companies listed in the Amman Stock Exchange for the period (2009-2020). To achieve the aims of the study, the panel-data approach was used. To test the hypotheses of the study, a multiple regression model using the panel corrected standard errors method was used, and the binary logistic regression method was used to process the selected data, in addition to a set of descriptive statistical methods. Accordingly, the study concluded that the female component in the Board of Directors is low and that there is a reverse impact of the accounting expertise of board members on dividends policy in industrial companies listed in the Amman Stock Exchange. No impact for gender diversity adjustment of the board members was found on the relationship of accounting expertise and dividends policy. Based on these results, the study recommends that industrial-sector companies appoint members with distinguished accounting expertise because of the impact of this expertise on dividends policy in line with the agency theory. It also recommends that current and future shareholders and investors when using financial reports should be interested in the presence of board members with accounting expertise, because this gives them special importance during the decision-making process.